Skrining Fitokimia dan Uji Aktivitas Sitotoksik dari Tumbuhan Sarang Semut (Myrmecodia beccarii Hook.f.) Asal Kabupaten Merauke - Modustriati P. Mardany; Linus Y. Chrystomo; Aditya K. Karim (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
Sarang semut (Myrmecodia beccarii Hook.f.) is a famous medicinal plant of Papua, which has traditionally potential in treating a wide variety of mild and severe illnesses, such as cancers and tumors, gout, coronary heart disease, hemorrhoids, tuberculosis, migraines, rheumatism, and leukemia. The purposes of this study were to determine the content of the active compound group and the cytotoxic activity of sarang semut plants from Merauke Region. The extraction was done by maceration using 96 % ethanol. The concentration of ethanolic extract were 0, 25, 50, 75, 100 ppm. The results of the study showed that the cytotoxic activity determine using BSLT (Brine Shrimp Lethality Test) method have a high cytotoxic activity with LC50 values of 22.86 ppm and containing the active compound namely flavonoids, tannins and saponins separately. The ethanolic extract of tuber of sarang semut (M. beccarii) has a high cytotoxic activity against larvae of Artemia salina Leach according BSLT method. Key words: Active compound, M. beccarii, cytotoxic activity, Merauke.